A Resistivity Investigation on Archean Metamorhics for Ground Water in Arid Zone - Chandrasekharan, H (Annals of Arid Zone, 2016)
Vertical Electrical Sounding (VES) surveys conducted at short intervals on a metamorphic region in western Rajasthan are presented. Results obtained are analysed both qualitatively and quantitatively in the light of available geological and hydrogeological information in order to locate ground water potential zones. Different aquifer and their nature are presented. It is found that most of the aquifer in the investigated area are associated with clays and silt. A concealed ridge has also been located in one of the two sections investigated.